Peranan Teknologi Konstruksi dalam Menunjang Pelaksanaan Operasi dan Pemeliharaan yang Berkelanjutan - Suprodjo Pusposutardjo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1994)
Insufficient involvement of O&M staffs' the design and construction stages, and the designers are not sufficiently alert to the requirement of O&M, indicate that the principle of water resources development as a unit system of operation and maintenance focussing on management have not been adopted in Indonesia. This condition causes weak linkage between construction and O&M, as indicated by unsuited structures to the local O&M capability. Low reliability of topographic map, complicated structural network, and insufficient data information on physical environment are also strongly influence on the unsuited structures to the O&M practice. Attempting to eliminate the problem, it is suggested that the adopted technology of construction has to be more flexible to accomodate the specific site requirements. As the complement of this effort the current administrative procedure of project implementation has to be revised in some ways so that the technology of construction transferable to O&M. By adopting this procedure of project implementation, technology of construction will have significant contribution in attaining sustainable O&M.